RELATIONSHIP AMONG LOCUS OF CONTROL, PERSONALITY AND ACADEMIC ACHIEVEMENT OF SECONDARY SCHOOL STUDENTS IN SOKOTO METOPOLIS - Haliru, Sadiya Magaji (Sokoto Educational Review, 2018)
The main purpose of this study was to determine the relationship among locus of control, personality and academic achievements of senior secondary Students in Sokoto metropolis. The samples were drawn from a total of 360 students in seven senior secondary schools purposively selected in Sokoto metropolis. For this study, adopted version of Olumolaye’s self-other motivation scale, an adopted version of Akimboye’s subscale A of adolescent personal data inventory and students’ JS III examination results of English, Mathematics, Integrated Science and Social studies to measure the variables of locus of control, personality and academic achievements. Four hypotheses were generated and tested in this study. Multiple regression analysis and Pearson product moment correlation coefficient were used to analyze data collected. Result of the study showed that there exist significant relationship among locus of control, personality and academic achievement, a significant relationship exists between the personality of students and their academic achievement. One of the recommendations of this study is that teachers and counsellors should attempt to handle students individually as students vary on the locus of control scale and personality.